Development and Validation of a Theoretical Model for Flexural Behavior in Timber-Concrete and Bamboo-Concrete Composite Beams - Thaís P. L. Siqueira; M’hamed Y. R. da Glória; Enzo Martinelli; Romildo D. Toledo Filho (Buildings, 2025)
The growing demand for sustainable construction has encouraged the use of composite beams combining timber or bamboo with concrete to optimize structural performance and reduce environmental impact. These hybrid systems, widely used in new constructions and retrofits, present modeling challenges due to the nonlinear interaction between materials and their mechanical connections. This study aims to develop and validate a finite element model to simulate the nonlinear flexural behavior of these composite beams. The model is based on an exact solution for two-layer elastic systems and incorporates nonlinear constitutive laws for concrete and timber/bamboo, along with a trilinear shear–slip law to represent interface behavior. Unlike most models, it is applicable to different connector types and a range of materials—including bamboo, timber, and both conventional and lightweight concrete. An incremental–iterative solution captures progressive deformations and failure mechanisms. Validation against 16 experimental beams showed accurate predictions of linear load capacity, mid-span deflection, and initial stiffness. Over 80% of the results showed deviations below 30%, and 50% were within 20%. The model also correctly captured the experimental failure mode in all cases. This approach provides a reliable and versatile tool for the structural analysis and design of composite beams.